Morphology-dependent pH-responsive release of hydrophilic payloads using biodegradable nanocarriers. Issue 64 (31st October 2018) - Pramanik, Sumit Kumar; Seneca, Senne; Peters, Martijn; D'Olieslaeger, Lien; Reekmans, Gunter; Vanderzande, Dirk; Adriaensens, Peter; Ethirajan, Anitha
Abstract : The morphology and release properties of aqueous core nanocapsules for the pH-responsive release of hydrophilic payload was investigated by systematically varying the number of biodegradable segments. Abstract : The development of functional nanocarriers with stimuli-responsive properties has advanced tremendously to serve biomedical applications such as drug delivery and regenerative medicine. However, the development of biodegradable nanocarriers that can be loaded with hydrophilic compounds and ensure its controlled release in response to changes in the surrounding environment still remains very challenging. Herein, we achieved such demands via the preparation of aqueous core nanocapsules using a base-catalyzed interfacial reaction employing a diisocyanate monomer and functional monomers/polymers containing thiol and hydroxyl functionalities at the droplet interface. pH-responsive poly(thiourethane–urethane) nanocarriers with ester linkages were synthesized by incorporating polycaprolactone diol, which is susceptible to hydrolytic degradation via ester linkages, as a functional monomer in the reaction formulation. We could demonstrate that by systematically varying the number of biodegradable segments, the morphology of the nanocarriers can be tuned without imparting the efficient encapsulation of hydrophilic payload (>85% encapsulation efficiency) and its transfer from organic to aqueous phase. The developed nanocarriers allow for a fast release of hydrophilic payload that depends on pH, the number of biodegradable segments and nanocarrier morphology. Succinctly put, this study provides important information to develop pH-responsive nanocarriers with tunable morphology, using interfacial reactions in the inverse miniemulsion process, by controlling the number of degradable segments to adjust the release profile depending on the type of application envisaged.